2001
DOI: 10.3354/dao047151
|View full text |Cite
|
Sign up to set email alerts
|

Experimental infection of white spot syndrome virus in freshwater crayfish Pacifastacus leniusculus

Abstract: The signal freshwater crayfish Pacifastacus leniusculus was found to be susceptible to infection with white spot syndrome virus (WSSV). Histopathological observations of various tissues of virus-injected crayfish showed similar symptoms to those from WSSV-infected penaeid shrimp, but no appearance of white spots on the cuticle or reddish body colour were observed, although these are the prominent gross signs of white spot disease in shrimp. A gene probe for detecting WSSV was developed in order to detect the v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
82
0
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(85 citation statements)
references
References 32 publications
2
82
0
1
Order By: Relevance
“…leniusculus, the proportion of GCs increased after an infection with white spot syndrome virus (WSSV) (Jiravanichpaisal et al, 2001;Liu et al, 2009). Taken together, several studies have clearly shown the importance of the hematopoietic process, such as induced synthesis, differentiation and the rapid release of cells during crustacean defense reactions against microbial infections.…”
Section: Reaction To Microbial Polysaccharides and Repeated Bleedingmentioning
confidence: 99%
“…leniusculus, the proportion of GCs increased after an infection with white spot syndrome virus (WSSV) (Jiravanichpaisal et al, 2001;Liu et al, 2009). Taken together, several studies have clearly shown the importance of the hematopoietic process, such as induced synthesis, differentiation and the rapid release of cells during crustacean defense reactions against microbial infections.…”
Section: Reaction To Microbial Polysaccharides and Repeated Bleedingmentioning
confidence: 99%
“…It infects several species of penaeid shrimp cultivated in the Eastern/Western Hemispheres (Lu et al 1997, Corsin et al 2001, in addition to a wide range of other decapods and crustaceans, including crabs (Chen et al 2000, Sahul Hameed et al 2001) and fresh water crayfish (Huang et al 2001, Jiravanichpaisal et al 2001. Several studies have confirmed that many suspected decapod carriers of WSSV can transmit the virus to Penaeus monodon (Wongteerasupaya et al 1996, Chang et al 1998, Wang et al 1998.…”
Section: Introductionmentioning
confidence: 97%
“…At least 18 cultured and/or wild penaeid shrimp (Park et al, 1998), eight caridean species (Pramod-Kiran et al, 2002), seven species of lobster (Rajendran et al, 1999), seven species of crayfish (Edgerton, 2004), 38 crab species (Yoganandhan et al, 2003) six non-decapod crustacean species (Hossain et al, 2001), members of the phyla Chaetognata and Rotifera (Yan et al, 2004), polychaete worms (Supak et al, 2005) and some aquatic insect larva (Ramírez-Douriet et al, 2005) have been found susceptible to the virus. Histopathological observations during WSV infection in brief is available regarding shrimp species such as Penaes monodon (Durand et al, 1997;Wang et al, 1999Wang et al, , 2000Mishra and Shekhar, 2005) Litopenaeus vannamei and Marsupenaeus japonicus (Lu et al, 1997;Lightner et al, 1998;Escobedo-Bonilla et al, 2007;Perez et al, 2005;Pantoja and Lightner, 2003), species of Crabs (Kanchanaphum et al, 1998;Kou et al, 1998) and lobster (Rajendran et al, 1999;Wang et al, 1998;Jiravanichpaisal et al, 2001).…”
Section: Introductionmentioning
confidence: 99%